STRATEGI BARU PENYULUHAN GIZI-KESEHATAN DALAM MENINGKATKAN PERILAKU SEHAT IBU SELAMA HAMIL DAN MENYUSUI - Jajah K. Husaini; Yekti Widodo; Salimar Salimar (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2001)
A New Strategy of Nutrition Education In Improving Health Behaviour of Pregnant and Lactating Women.Background: The new health paradigm of the year 2010 is emphasizing on preventive and promotive measures through the improvement of health behavior of the population. On the same time, the economic crisis has worsened the nutritional status, particularly for pregnant and lactating women, leading to increase of malnutrition and mortality among infants and women. Programs in improving health behavior, particularly in many nutrition programs, have poorly designed and poorly implemented at grass root levels and therefore may not assess nutrition knowledge, attitude and practice prroperty, with the consequence that the results may have little meanings.Objective: The aim of the study was to examine model of empowering pregnant and lactating women through, the improvement of heatlh and nutriton behavior by using the method of Women's Contact. Women's Contact or Kontak Ibu was a trained person who always give services to pregnant and lactating women, including midwives, traditional birth attendants, community volunteers, such as ceders, etc.Methods: The study areas were located in Bogor and Tangerang Districts. In the treatment group areas 21 Kontak Ibu were trained for 2 days in improving their skills in nutrition and heatlh education and supervised. In the control group areas 20 Kontak Ibu were trained for 1 day and Without supervised during the 4 months of intervention period. The material of nutrition and heatlh education developed by the previous study, was provided for all Kontak Ibu. In the treatment area 80 women (40 pregnant and 40 lactating) received the services given by Kontak Ibu. The same number and proportion of women also received the services in control areas.Results: The performance of Kontak Ibu in the treatment areas generally better than in the control areas in term of the frequency of giving education, number of women receiving services, referral forms completed, and number of targeted women visited. The women who improved their practices in solving the problem of morning sickness and low appetite for pregnant women, and problem of eating and diarrhea for infants were significantly (p<0.05) higher in the treatment than in the control group. Other practices, such as solving problem of headache, edema, vances. fever, etc. were improved in both groups.Conclusion: It is found in both group the new service strategy using method of Kontak Ibu changed several behaviors among women in communites. The changes in the experiment group were more remarkable than in the control group.Suggestion: The strategies of Kontak Ibu services changed behavior of both the service providers ard the women seeking services. It is therefore likely that application of the model Kontak Ibu services could be implemented in the existing nutrition improvement programs.Key words: nutrition education, behavior, pregnant and lactating women, women's contract